Empirical Assessment of Expectations Associated with the Recent Discovery of Commercialisable Oil in Ghana - Kwarteng Ernest; Kumi Ernest; Yeboah Asuamah Samuel (International Review of Management and Marketing, 2012)
The paper aim at assessing empirically the various expectations held by people in the economy in the face of oil revenue in order to contribute to the body of knowledge that exist in expectation formation. The study is based on descriptive quantitative survey of students in first and third year marketing department of Sunyani Polytechnic offering Higher National Diploma programme. A sample size of 70 respondents was used and was selected using non probability (convenience) sampling method. Questionnaires were prepared using the Likert scale and were distributed to the students. Data were analysed using SPSS and the result presented in tables. Results indicate that respondents hold mixed expectation in the face of the oil revenue. There was gender, age, religion, employment differences in some of the expectations held by respondents. Future research should look at issues such as why there are these differences in opinions and the effect of macroeconomic variables such as inflation, GDP on public confidence as well as ways of managing these expectations.